Synthesis and Properties of BaMTeS (M = Fe, Mn, Zn) and the Disordered Structural Analog BaGe0.5TeS - Frøen, Emil H.; Nowak, Domenic; Adler, Peter; Valldor, Martin (Inorganic chemistry, 2024)
A series of tertiary sulfide-tellurides, BaM x TeS (M = Fe, Mn, Zn, Ge), has been synthesized by solid-state synthesis. The compounds assume an orthorhombic crystal structure, described by the Cmcm (No. 63) space group, and are structural analogs of the BaMSO (M = Co, Zn) phases. The properties of all four analogs are investigated by DFT analysis. As only the BaFeTeS analog was prepared as a relatively pure phase, this homologue was subject to further experimental investigations, including heat capacity, magnetometry, and Mössbauer spectroscopy. BaFeTeS exhibits no obvious phase transition between 2 and 300 K, has no paramagnetic behavior, and lacks long-range magnetic ordering. However, the Mössbauer spectra, as well as electrical resistance data, indicate a hidden transition near 200 K that is tentatively explained by a dynamic charge-density-wave mechanism, based on a resonating valence bond (RVB) model.